The impact of ageing, inequality and the evolution of morbidity on future health expenditure - Thomas Horvath; Thomas Leoni; Martin Spielauer; Peter Reschenhofer (Austrian Institute of Economic Research (WIFO), 2024)
Population ageing is associated with increasing healthcare expenditure. To guide policy and the adaptation of health systems, however, a more accurate understanding of the quantitative effect of different components of ageing and other factors that influence cost dynamics is needed. This study uses dynamic microsimulation modelling to project healthcare expenditure and disentangle the impact of changes in longevity, population age-structure, healthy life years and socioeconomic health inequalities in Austria. Combining price weights for healthcare services with information on healthcare consumption from the Austrian Health Interview Survey, we calculate average cost profiles by gender, age, and education consistent with the aggregate System of Health Accounts. These cost profiles are then combined with official population projections in the microsimulation model microDEMS to project different expenditure scenarios for the Austrian population up to the year 2060. We calculate total and per-capita cost trajectories and assess their economic impact by contrasting them with two different indicators for the size of the labour force. All our scenarios indicate that demographic ageing is likely to increase future healthcare costs, even if we assume a compression of morbidity over time. Reducing socioeconomic inequalities in health can contribute significantly to mitigate the cost dynamics resulting from demographic change. In economic terms, costs per person of working age increase by between 12 and 48 percent, depending on the scenario. When contrasted with changes in the number of economically active people, however, the increase is around 7 to 9 percentage points lower.
Keywords: 330; healthcare expenditure; ageing; microsimulation; projections